Preparation and application of a water-based graphene oxide / polyaniline composite hybrid
By using solvent dispersion and emulsification technology in the preparation process of graphene oxide/polyaniline composite hybrid, the problem of insufficient uniform dispersion and stability of polyaniline particles is solved, and the capacitance and corrosion resistance of the composite material are improved.
Patent Information
- Application Number
- CN202311651144.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-04
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-12-04
AI Technical Summary
The preparation process of existing graphene oxide/polyaniline composite hybrids is complicated, and the uniform dispersion and stability of polyaniline particles are insufficient, which affects their capacitance and corrosion resistance.
Use a suitable solvent to disperse the polyaniline powder to obtain the polyaniline solution as the oil phase, add the aqueous dispersion of the graphene oxide in the aqueous dispersion of the water dispersion of the graphene oxide and emulsify, and complete the nanoassembly between graphene oxide and polyaniline by solvent evaporation or water washing and centrifugation. , a water-dispersed and stable graphene oxide/polyaniline composite hybrid was obtained.
The capacitance performance and cycle life of graphene oxide/polyaniline composite hybrid is improved, and its corrosion resistance and corrosion resistance in aqueous epoxy resins are enhanced.
Smart Images

Figure CN117820859B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation and application of an aqueous graphene oxide / polyaniline composite hybrid, and belongs to the field of functional material application. Background Art
[0002] Graphene has a high specific surface area and excellent electrical conductivity. In recent years, it has shown broad application prospects in nanoelectronics and energy storage. It is a promising supercapacitor electrode material. However, the capacitance of carbon materials is attributed to the double electric layer at the electrode / electrolyte interface, which is highly dependent on the specific area of the electrode. Due to the inevitable aggregation of graphene nanosheets, graphene nanomaterials do not achieve ideal capacitance performance. In addition, due to the high specific surface area and excellent barrier ability of graphene, it can be added to water-based epoxy resin to improve the anti-corrosion performance of epoxy resin. However, during long-term use, it is difficult for graphene composite coatings to eliminate the grain boundary defects on graphene. These defects will form galvanic couples between the anode metal substrate and the cathode graphene, leading to local corrosion, which limits the functional application of water-based anti-corrosion coatings.
[0003] Conductive polymers such as polyaniline often show higher capacitance in supercapacitors, but their poor cycle life limits their practical application in supercapacitors. In addition, after polyaniline (PANI) is deposited on some metal surfaces, it can passivate the metal and produce anodic protection, making it suitable for use in the field of anti-corrosion coatings. However, the characteristics of polyaniline such as difficulty in processing and easy agglomeration have greatly affected its performance and application in anti-corrosion coatings.
[0004] In order to avoid the shortcomings of a single material, graphene oxide and polyaniline are combined to prepare a hybrid. The resulting composite hybrid not only has electrochemical properties such as high capacitance and high cycle life, but also can synergistically promote the anti-corrosion performance of water-based anti-corrosion coatings when added to some water-based epoxy resins, greatly improving the processing and application of materials.
[0005] At present, the conventional graphene oxide / polyaniline composite hybridization process is to mix a hydrochloric acid solution of aniline and a hydrochloric acid solution of graphene oxide, and then perform in-situ polymerization to obtain; it requires a chemical reaction, the operation is complicated, and the requirements are high (CN116948518 A), and the uniform dispersibility and stability of the polyaniline particles in the prepared graphene oxide / polyaniline composite hybrid need to be improved. How to ensure that polyaniline and graphene oxide can be effectively assembled, greatly improve the capacitance performance of the hybrid, and evenly disperse in water-based epoxy resin to improve its anti-corrosion performance is a technical problem that needs to be solved urgently. Summary of the invention
[0006] [Technical issues]
[0007] When graphene oxide and polyaniline are used to prepare composite hybrids, they are basically prepared by in-situ polymerization by adding aniline, which is a complicated operation.
[0008] [Technical solution]
[0009] In order to solve at least one of the above problems, the present invention provides a water-based graphene oxide / polyaniline composite hybrid and its preparation and application. The present invention uses a suitable solvent to disperse polyaniline powder to obtain a polyaniline solution as an oil phase, and then adds it to the water-dispersed phase graphene oxide aqueous dispersion for stirring and emulsification. After solvent evaporation or water washing and centrifugation, the nano-assembly between graphene oxide and polyaniline is completed to obtain a water-dispersible and stable graphene oxide / polyaniline composite hybrid; then it is compounded with a water-based epoxy resin to obtain a water-based epoxy resin anti-corrosion coating based on a composite modification of graphene oxide / polyaniline. The graphene oxide / polyaniline composite hybrid prepared by the present invention can be prepared into a flexible electrode film, which has a high specific capacitance and a long cycle life in the application process of supercapacitors. The prepared water-based graphene oxide / polyaniline modified epoxy resin anti-corrosion coating has excellent water dispersion stability and corrosion resistance.
[0010] The first object of the present invention is to provide a method for preparing an aqueous graphene oxide / polyaniline composite hybrid, comprising the following steps:
[0011] (1) Oil phase:
[0012] Ultrasonic dispersion of polyaniline powder in a solvent to obtain a polyaniline solution; wherein the solvent is a single phenolic solvent or a mixed solvent of a phenolic solvent and a low dielectric constant solvent as an oil phase;
[0013] (2) Aqueous Dispersed Phase:
[0014] dispersing graphene oxide in water to obtain a graphene oxide aqueous dispersion as an aqueous dispersed phase;
[0015] (3) Preparation of hybrids:
[0016] The polyaniline solution is added to the graphene oxide aqueous dispersion, stirred and ultrasonicated to obtain an oil-in-water emulsion; then the oil-in-water emulsion is subjected to solvent evaporation or centrifugal washing to obtain an aqueous graphene oxide / polyaniline composite hybrid.
[0017] In one embodiment of the present invention, the particle size of the polyaniline in step (1) is 5-8 μm, sulfonic acid doped, and conductive.
[0018] In one embodiment of the present invention, the concentration of the polyaniline solution in step (1) is 5-10 mg / mL.
[0019] In one embodiment of the present invention, the ultrasonic dispersion in step (1) is water bath ultrasonic dispersion, specifically, ultrasonic treatment at 15-25W, 20-30°C (normal temperature) for 15-20min.
[0020] In one embodiment of the present invention, the phenol solvent in step (1) is any one or more of m-cresol, o-cresol, p-cresol, and resorcinol; the low dielectric constant solvent is one or more of n-hexane, 1,4-dioxane, toluene, anisole, and chloroform.
[0021] In one embodiment of the present invention, the mass ratio of the phenol solvent to the low dielectric constant solvent in the mixed solvent of the phenol solvent and the low dielectric constant solvent in step (1) is 3-5:1.
[0022] In one embodiment of the present invention, the preparation method of the graphene oxide aqueous dispersion in step (2) is:
[0023] The graphene oxide filter cake was added to water at a concentration of 5-10 mg / mL, and ultrasonically treated at 15-25 W and 20-30° C. (normal temperature) for 15-20 min, and washed and centrifuged at 10000 rpm-11000 rpm for 10-20 min to obtain graphene oxide with a pH of 4-9;
[0024] dispersing graphene oxide in water to obtain a graphene oxide aqueous dispersion;
[0025] Among them, water washing and centrifugation are 1 to 4 times.
[0026] In a preferred embodiment, the pH of the graphene oxide aqueous dispersion in step (2) is 5-6.
[0027] In one embodiment of the present invention, the concentration of the graphene oxide aqueous dispersion in step (2) is 0.1-1 mg / mL.
[0028] In one embodiment of the present invention, the volume ratio of the polyaniline solution to the graphene oxide aqueous dispersion in step (3) is 8-720:800.
[0029] In one embodiment of the present invention, the addition in step (3) is carried out dropwise at a rate of 0.8-1.2 mL / min.
[0030] In one embodiment of the present invention, the stirring in step (3) is performed while adding dropwise, specifically, stirring at 3000-4000 rpm and 20-30° C. (normal temperature) for 20-30 min.
[0031] In one embodiment of the present invention, the ultrasound in step (3) is performed at 100-300W and 20-30°C (normal temperature) for 5-10 min.
[0032] In one embodiment of the present invention, the centrifugal washing in step (3) is performed at 10000 rpm-11000 rpm for 10-20 min, and the number of centrifugation is 1-3 times.
[0033] The second object of the present invention is the aqueous graphene oxide / polyaniline composite hybrid prepared by the method described in the present invention.
[0034] The third object of the present invention is to provide a method for preparing a graphene oxide / polyaniline composite modified waterborne epoxy resin anticorrosive coating, comprising the following steps:
[0035] S1: dispersing the aqueous graphene oxide / polyaniline composite hybrid into water to obtain a graphene oxide / polyaniline composite hybrid solution;
[0036] S2: Add the graphene oxide / polyaniline composite hybrid solution dropwise into the epoxy emulsion and mix evenly; then add the water-based epoxy curing agent solution and stir evenly to obtain a graphene oxide / polyaniline composite modified water-based epoxy resin anti-corrosion coating.
[0037] In one embodiment of the present invention, the concentration of the graphene oxide / polyaniline composite hybrid solution in S1 is 1-10 mg / mL.
[0038] In one embodiment of the present invention, the mass ratio of the graphene oxide / polyaniline composite hybrid solution to the epoxy emulsion in S2 is 3-12:20.
[0039] In one embodiment of the present invention, the solid content of the epoxy emulsion in S2 is 40-60%.
[0040] In one embodiment of the present invention, the dropwise adding speed in S2 is 0.8-1.2 mL / min.
[0041] In one embodiment of the present invention, the uniform mixing in S2 is carried out by stirring at 20-30° C. (normal temperature) and 3000-4000 rpm for 2-4 hours.
[0042] In one embodiment of the present invention, the mass ratio of the epoxy emulsion to the aqueous epoxy curing agent solution in S2 is 20:3-4.
[0043] In one embodiment of the present invention, the solid content of the aqueous epoxy curing agent solution in S2 is 40-60%.
[0044] In one embodiment of the present invention, S2 is stirred evenly at 3000-4000 rpm and 20-30° C. (normal temperature) for 20-40 min.
[0045] The fourth objective of the present invention is a water-based epoxy resin anti-corrosion coating compositely modified with graphene oxide / polyaniline prepared by the method described in the present invention.
[0046] The fifth object of the present invention is to use the graphene oxide / polyaniline composite modified water-based epoxy resin anti-corrosion coating in the field of metal corrosion protection.
[0047] In one embodiment of the present invention, the metal corrosion protection includes the field of building equipment.
[0048] A sixth object of the present invention is to provide a supercapacitor, which uses the aqueous graphene oxide / polyaniline composite hybrid described in the present invention.
[0049] In one embodiment of the present invention, the supercapacitor uses the aqueous graphene oxide / polyaniline composite hybrid of the present invention;
[0050] Specifically, water is added to the aqueous graphene oxide / polyaniline composite hybrid to prepare a solution with a concentration of 1-10 mg / mL, and then vacuum filtered to prepare the graphene oxide / polyaniline composite hybrid flexible electrode membrane.
[0051] In one embodiment of the present invention, the prepared graphene oxide / polyaniline composite hybrid flexible electrode film has a thickness of 10-25 μm.
[0052] A seventh object of the present invention is to provide a method for improving the dispersibility of polyaniline in an oxide graphite dispersion, comprising the following steps:
[0053] (1) Oil phase:
[0054] Ultrasonic dispersion of polyaniline powder in a solvent to obtain a polyaniline solution; wherein the solvent is a single phenolic solvent or a mixed solvent of a phenolic solvent and a low dielectric constant solvent as an oil phase;
[0055] (2) Aqueous Dispersed Phase:
[0056] dispersing graphene oxide in water to obtain a graphene oxide aqueous dispersion as an aqueous dispersed phase;
[0057] (3) Preparation of hybrids:
[0058] The polyaniline solution is added to the graphene oxide aqueous dispersion, stirred and ultrasonicated to obtain an oil-in-water emulsion; then the oil-in-water emulsion is subjected to solvent evaporation or centrifugal washing to obtain an aqueous graphene oxide / polyaniline composite hybrid.
[0059] [Beneficial Effects]
[0060] (1) The present invention uses a graphene oxide aqueous dispersion as a water dispersion phase and a polyaniline solution as an oil phase for uniform mixing and stirring to prepare a uniform and stable water-in-oil emulsion. Thousands of small oil droplets are stabilized by graphene oxide as an emulsifier, which facilitates the subsequent nano-assembly between graphene oxide and polyaniline, and greatly increases the interaction efficiency between graphene oxide and polyaniline; then, after solvent evaporation or centrifugal washing, an aqueous graphene oxide / polyaniline composite hybrid is obtained.
[0061] (2) In the process of preparing the aqueous graphene oxide / polyaniline hybrid of the present invention, the solvent is removed by evaporation or water washing and centrifugation, and the dispersion medium is dehydrated, which greatly reduces the pollution to the environment.
[0062] (3) The present invention assembles polyaniline materials on the surface of graphene oxide and between the sheets, which can effectively reduce the stacking of graphene oxide itself and improve the uniform dispersion of polyaniline, dispersing polyaniline into nanometer-level particle sizes, which greatly improves the capacitance performance and cycle life of the composite hybrid material.
[0063] (4) The present invention assembles polyaniline nanomaterials on the surface of graphene oxide, which can effectively reduce the stacking and agglomeration of graphene oxide in epoxy resin and improve the uniform dispersibility of polyaniline; at the same time, graphene oxide has abundant hydrophilic functional groups, which can promote the uniform dispersion of graphene oxide in water-based coatings. The water-based graphene oxide / polyaniline modified epoxy resin anticorrosive coating prepared by the present invention has excellent water dispersion stability and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a SEM image of the polyaniline powder used in the example, where A: 5 μm, B: 1 μm.
[0065] Figure 2 This is the SEM cross-sectional image of the aqueous graphene oxide / polyaniline composite hybrid GO / PANI (9 / 1) prepared in Example 1, wherein A: 5 μm, B: 1 μm.
[0066] Figure 3 These are photos of the aqueous graphene oxide / polyaniline composite hybrid solution prepared in Example 1 after being placed for 6 months, wherein A is a photo placed upright after being inverted; and B is a photo placed upside down after being inverted.
[0067] Figure 4 This is the SEM cross-sectional image of the aqueous graphene oxide / polyaniline composite hybrid GO / PANI (9 / 1)-direct dispersion in Comparative Example 1, where A: 5 μm, B: 1 μm.
[0068] Figure 5This is a photograph of the aqueous graphene oxide / polyaniline composite hybrid solution prepared in Comparative Example 1 after being placed for 1 month.
[0069] Figure 6 This is the SEM cross-sectional image of the aqueous graphene oxide / polyaniline composite hybrid prepared in Comparative Example 2.
[0070] Figure 7 This is the SEM cross-sectional image of the aqueous graphene oxide / polyaniline composite hybrid prepared in Comparative Example 3.
[0071] Figure 8 This is a SEM cross-sectional image of the aqueous graphene oxide / polyaniline composite hybrid prepared in Comparative Example 4.
[0072] Fig. 9 This is a test chart of the anti-corrosion performance of the graphene oxide / polyaniline composite modified water-based epoxy resin anti-corrosion coating prepared in Example 3, Example 4 and Comparative Example 5.
[0073] Fig.10 This is a test chart of the anti-corrosion performance of the graphene oxide / polyaniline composite modified water-based epoxy resin anti-corrosion coating prepared in Example 4, Example 5 and Comparative Example 5 and Comparative Example 6.
[0074] Fig.11 These are the supercapacitor test diagrams of Example 6, wherein A is an electrochemical cyclic voltammetry test diagram, and B is an electrochemical impedance spectroscopy test diagram. DETAILED DESCRIPTION
[0075] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0076] Test method:
[0077] 1. Anti-corrosion performance test:
[0078] The coating was prepared on a standard carbon steel plate using a scraper (250 μm) (and then dried and cured at room temperature). After a 40-day salt spray test in a neutral salt solution of 3.5% by mass NaCl, the coating surface was observed to see if rust occurred.
[0079] 2. Dispersion (stability) test:
[0080] The solution was left to stand for several months to observe whether there was any precipitation, stratification or flocculation.
[0081] 3. Dispersion uniformity test:
[0082] Scanning electron microscopy (SEM) was used to observe the microstructure and arrangement of the waterborne graphene / polyaniline composite hybrid and evaluate the uniformity of the dispersion of waterborne graphene and polyaniline.
[0083] 4. Supercapacitor performance test:
[0084] A three-electrode system was used, with the flexible electrode film prepared from graphene oxide / polyaniline hybrid as the working electrode, the carbon black film as the counter electrode, Ag / AgCL as the reference electrode, and the electrolyte solution using 1 mol / L sulfuric acid solution at 20 mV·S -1 Cyclic voltammetry was performed at a scan rate of ; impedance testing was performed at a voltage of 10 mV and a frequency of 0.1-50000 Hz.
[0085] The raw materials used in the examples are:
[0086] Graphene oxide filter cake: pH = 2-5, size <10 μm, purchased from Changzhou Sixth Element Material Technology Co., Ltd.
[0087] Polyaniline powder: particle size 5-8 μm, sulfonic acid doped, conductive, purity >98%, purchased from Sigma-Aldrich.
[0088] Epoxy emulsion: BANCO 2095, non-ionic epoxy resin, solid content 50%, purchased from Lian Gu New Material Technology Co., Ltd.
[0089] Water-based epoxy curing agent: BANCO 919, a non-ionic modified amine water-based epoxy curing agent, with a solid content of 50%, can be cured at room temperature, purchased from Lian Gu New Materials Technology Co., Ltd.
[0090] In the examples and comparative examples, the reaction temperature was not specifically specified or the reaction temperature was 25°C.
[0091] Example 1
[0092] A method for preparing an aqueous graphene oxide / polyaniline composite hybrid comprises the following steps:
[0093] (1) Oil phase:
[0094] 0.5 g of polyaniline powder was added to 100 g of a mixed solvent of m-cresol and 1,4-dioxane (mass ratio was 4:1), and ultrasonically dispersed for 15 min at 20 W and 25° C. (room temperature) using an ultrasonic cleaning machine to obtain a polyaniline solution;
[0095] (2) Aqueous Dispersed Phase:
[0096] The graphene oxide filter cake was dispersed in water to form a 10 mg / mL aqueous dispersion, and then ultrasonicated in a water bath at 20W and 25°C for 20 minutes using an ultrasonic cleaner, and then washed and centrifuged at 10,000 rpm for 15 minutes, and the washing and centrifugation were repeated 3 times to obtain graphene oxide with a pH of 5;
[0097] Dispersing graphene oxide at a pH of 5 in water to obtain a 0.5 mg / mL graphene oxide aqueous dispersion;
[0098] (3) Preparation of hybrids:
[0099] 800 mL of graphene oxide aqueous dispersion was taken into a 1000 mL three-necked flask, stirred at 3500 rpm and 25°C (room temperature), and then 8.89 mL of polyaniline solution was added dropwise at a dropping speed of 1 mL / min. Stirring was continued for 30 min, and then a cell disruptor was used for ultrasonication at 200 W and room temperature (25°C) for 10 min; then, the mixture was washed and centrifuged at 10000 rpm for 15 min, and the washing and centrifugation were repeated twice to obtain an aqueous graphene oxide / polyaniline composite hybrid, recorded as GO / PANI (9 / 1).
[0100] Figure 1 This is the SEM image of polyaniline powder. Figure 1 It can be seen that the original polyaniline powder is severely agglomerated and has a large size, which leads to its poor dispersibility and low utilization efficiency in traditional water-based anti-corrosion coatings, greatly limiting the application of polyaniline in water-based anti-corrosion coatings.
[0101] Figure 2 This is the SEM cross-sectional image of aqueous graphene oxide / polyaniline GO / PANI (9 / 1) in Example 1. Figure 2 It can be seen that the water-based graphene oxide / polyaniline slurry prepared in Example 1 has an ideal and orderly structural arrangement. Polyaniline is dispersed into very small nanoparticles during the operation and treatment process, and is regularly and orderly arranged on the surface of graphene oxide. The two can produce a synergistic effect to jointly enhance the corrosion resistance of water-based epoxy resin, thereby preparing a water-based high-performance graphene oxide / polyaniline anti-corrosion coating.
[0102] The aqueous graphene oxide / polyaniline composite hybrid GO / PANI (9 / 1) was dispersed in water to obtain a 1 mg / mL aqueous graphene oxide / polyaniline composite hybrid solution. Then, it was placed at room temperature for 6 months and the solution was inverted. Figure 3 :
[0103] from Figure 3 It can be seen that the water dispersion of the composite hybrid solution is stable and no material precipitation or sinking occurs for a long time, and the graphene oxide / polyaniline composite hybrid is well dispersed.
[0104] Example 2
[0105] The amount of carbon nanotube dispersion in step (3) of Example 1 was adjusted to 34.29, 80, 186.67, and 720 mL, and the rest was consistent with Example 2 to obtain aqueous graphene oxide / polyaniline composite hybrids, recorded as GO / PANI (7 / 3), GO / PANI (1 / 1), GO / PANI (3 / 7), and GO / PANI (1 / 9).
[0106] The obtained waterborne graphene / polyaniline composite hybrid was subjected to elemental analysis test, and the actual interaction ratio of the obtained graphene / polyaniline composite hybrid was calculated according to the elemental test results. The calculation results are as follows:
[0107] It can be seen from Table 1 that the actual interaction ratio between graphene oxide and polyaniline in the water-based graphene / polyaniline composite hybrid GO / PANI (9 / 1) obtained in Example 1 is closest to the feed ratio during elemental analysis, and the loss of graphene oxide and polyaniline is reduced to a minimum during the preparation process. The interaction between the two can be intuitively reflected through the feed ratio.
[0108] Table 1
[0109] Dosage Graphene oxide (%) Polyaniline (%) 8.89 (Example 1, GO / PANI (9 / 1)) 89.07 10.93 34.29(GO / PANI(7 / 3)) 76.65 23.35 80(GO / PANI(1 / 1)) 62.28 37.72 186.67(GO / PANI(3 / 7)) 19.01 80.99 720(GO / PANI(1 / 9)) 4.04 95.96
[0110] Comparative Example 1 Direct Dispersion
[0111] A method for preparing an aqueous graphene oxide / polyaniline composite hybrid comprises the following steps:
[0112] (1) The graphene oxide filter cake is dispersed in water to form a 10 mg / mL aqueous dispersion, and then ultrasonicated in a water bath at 20W and 25°C for 20 minutes using an ultrasonic cleaner, and then washed and centrifuged at 10,000 rpm for 15 minutes, and the washing and centrifugation are repeated 3 times to obtain graphene oxide with a pH of 5; the graphene oxide with a pH of 5 is dispersed in water to obtain a 0.5 mg / mL aqueous dispersion of graphene oxide;
[0113] (2) 800 mL of graphene oxide aqueous dispersion was taken into a 1000 mL beaker, and then 0.045 g of polyaniline powder was added. The mixture was stirred evenly with a glass rod, and ultrasonicated in a water bath at 25°C for 2 h using an ultrasonic cleaner at 20 W. The mixture was then ultrasonicated at a power of 200 W using an ultrasonic cell crusher for 2 h. The mixture was then washed and centrifuged at 10,000 rpm for 15 min. The washing and centrifugation were repeated twice to obtain an aqueous graphene oxide / polyaniline composite hybrid, which was recorded as GO / PANI (9 / 1)-direct dispersion.
[0114] SEM cross-section of aqueous graphene oxide / polyaniline GO / PANI (9 / 1)-direct dispersion Figure 4As shown, although graphene oxide and polyaniline interact with each other in the conjugated region, polyaniline still agglomerates in the water-based graphene oxide / polyaniline GO / PANI (9 / 1)-direct dispersion sample prepared by the method of Comparative Example 1, and the size is relatively large. The aggregated polyaniline is intercalated in the graphene oxide sheet, making it difficult for graphene oxide and polyaniline to synergistically enhance the corrosion resistance of water-based epoxy resin.
[0115] The aqueous graphene oxide / polyaniline composite hybrid (GO / PANI (9 / 1)-direct dispersion) prepared in Comparative Example 1 was dispersed in water to obtain a 1 mg / mL aqueous graphene oxide / polyaniline composite hybrid solution.
[0116] Figure 5 This is a digital photo of the prepared aqueous graphene oxide / polyaniline composite hybrid solution after being placed for 1 month. Figure 5 It can be seen that the water dispersion of the composite hybrid solution is unstable, and the solution will be stratified and sink to the bottom after being placed for a long time. The dispersion effect of the graphene oxide / polyaniline composite hybrid is poor.
[0117] Comparative Example 2: Different dispersion solvents
[0118] A method for preparing an aqueous graphene oxide / polyaniline composite hybrid comprises the following steps;
[0119] (1) Oil phase:
[0120] 0.5 g of polyaniline powder was added to 100 g of NMP (N-methylpyrrolidone), and ultrasonically dispersed for 20 min at 20 W and 25° C. (normal temperature) using an ultrasonic cleaning machine to obtain a polyaniline solution;
[0121] (2) Aqueous Dispersed Phase:
[0122] The graphene oxide filter cake was dispersed in water to form a 10 mg / mL aqueous dispersion, and then ultrasonicated in a water bath at 20W and 25°C for 20 minutes using an ultrasonic cleaner, and then washed and centrifuged at 10,000 rpm for 15 minutes, and the washing and centrifugation were repeated 3 times to obtain graphene oxide with a pH of 5;
[0123] Dispersing graphene oxide at a pH of 5 in water to obtain a 0.5 mg / mL graphene oxide aqueous dispersion;
[0124] (3) Preparation of hybrids:
[0125] 800 mL of graphene oxide aqueous dispersion was taken into a 2000 mL three-necked flask, stirred at 3500 rpm and 25°C (room temperature), and then 8.89 mL of polyaniline dispersion was added dropwise, and stirring was continued for 30 min. Then, a cell disruptor was used for ultrasonication at 200 W and room temperature (25°C) for 20 min, and then centrifuged and washed at 10000 rpm for 15 min. The centrifugal washing was repeated twice to obtain an aqueous graphene oxide / polyaniline composite hybrid.
[0126] The SEM cross-sectional image of the prepared aqueous graphene oxide / polyaniline composite hybrid is shown in Figure 6 As shown, from Figure 6 It can be seen that in the aqueous graphene oxide / polyaniline sample prepared by the method of Comparative Example 2, polyaniline is seriously aggregated and has a large size. The aggregated polyaniline is intercalated in the graphene oxide sheet, and the sheet structure of the graphene oxide is also destroyed.
[0127] Comparative Example 3: Different Dispersing Solvents
[0128] A method for preparing an aqueous graphene oxide / polyaniline composite hybrid comprises the following steps;
[0129] (1) Oil phase:
[0130] 0.5 g of polyaniline powder was added to 100 g of a mixed solvent of m-cresol and acetone (mass ratio was 4:1), and ultrasonically dispersed for 15 min at 20 W and 25° C. (room temperature) using an ultrasonic cleaning machine to obtain a polyaniline solution;
[0131] (2) Aqueous Dispersed Phase:
[0132] The graphene oxide filter cake was dispersed in water to form a 10 mg / mL aqueous dispersion, and then ultrasonicated in a water bath at 20W and 25°C for 20 minutes using an ultrasonic cleaner, and then washed and centrifuged at 10,000 rpm for 15 minutes, and the washing and centrifugation were repeated 3 times to obtain graphene oxide with a pH of 5;
[0133] Dispersing graphene oxide at a pH of 5 in water to obtain a 0.5 mg / mL graphene oxide aqueous dispersion;
[0134] (3) Preparation of hybrids:
[0135] 800 mL of graphene oxide aqueous dispersion was taken into a 2000 mL three-necked flask, stirred at 3500 rpm and 25 ° C (room temperature), and then 8.89 mL of polyaniline dispersion was added dropwise, and stirring was continued for 30 min. Then, a cell disruptor was used for ultrasonication at 200 W and room temperature (25 ° C) for 10 min, and then centrifuged and washed at 10000 rpm for 15 min. The centrifugal washing was repeated twice to obtain an aqueous graphene oxide / polyaniline composite hybrid.
[0136] The SEM cross-sectional image of the prepared aqueous graphene oxide / polyaniline composite hybrid is shown in Figure 7 As shown, from Figure 7 It can be seen that in the aqueous graphene oxide / polyaniline sample prepared by the method of Comparative Example 3, polyaniline is seriously aggregated and has a large size. The aggregated polyaniline is intercalated in the graphene oxide sheet, and the sheet structure of the graphene oxide is also destroyed.
[0137] Comparative Example 4 Direct Mixing
[0138] A method for preparing an aqueous graphene oxide / polyaniline composite hybrid comprises the following steps;
[0139] (1) Oil phase:
[0140] 0.5 g of polyaniline powder was added to 100 g of a mixed solvent of m-cresol and 1,4-dioxane (mass ratio was 4:1), and ultrasonically dispersed for 15 min at 20 W and 25° C. (room temperature) using an ultrasonic cleaning machine to obtain a polyaniline solution;
[0141] (2) Aqueous Dispersed Phase:
[0142] The graphene oxide filter cake was dispersed in water to form a 10 mg / mL aqueous dispersion, and then ultrasonicated in a water bath at 20W and 25°C for 20 minutes using an ultrasonic cleaner, and then washed and centrifuged at 10,000 rpm for 15 minutes, and the washing and centrifugation were repeated 3 times to obtain graphene oxide with a pH of 5;
[0143] Dispersing graphene oxide at a pH of 5 in water to obtain a 0.5 mg / mL graphene oxide aqueous dispersion;
[0144] (3) Preparation of hybrids:
[0145] 800 mL of graphene oxide aqueous dispersion was taken into a 2000 mL three-necked flask, stirred at 3500 rpm and 25°C (room temperature), and then 8.89 mL of polyaniline solution was directly added, and stirring was continued for 30 min. Then, a cell disruptor was used for ultrasonication at 200 W and room temperature (25°C) for 10 min, and then centrifuged and washed at 10000 rpm for 15 min. The centrifugal washing was repeated twice to obtain an aqueous graphene oxide / polyaniline composite hybrid, recorded as GO / PANI (9 / 1).
[0146] The SEM cross-sectional image of the prepared aqueous graphene oxide / polyaniline composite hybrid is shown in Figure 8 As shown, from Figure 8 It can be seen that the polyaniline in the aqueous graphene oxide / polyaniline sample prepared by the method of Comparative Example 4 is seriously agglomerated, and directly adding the dispersed polyaniline oil solution fails to achieve good dispersion in the aqueous medium.
[0147] Example 3
[0148] A method for preparing a graphene oxide / polyaniline composite-modified water-based epoxy resin anti-corrosion coating comprises the following steps:
[0149] S1: dispersing the aqueous graphene oxide / polyaniline composite hybrid prepared in Example 1 into water to obtain a graphene oxide / polyaniline composite hybrid solution with a concentration of 8 mg / mL;
[0150] S2: Add 20g of epoxy emulsion into a 100mL three-necked flask, take 3.76g of graphene oxide / polyaniline composite hybrid solution and add it dropwise into the epoxy emulsion, stir at 3500rpm and 25°C (room temperature) for 3h to obtain a mixed solution; then add 3.82g of water-based epoxy curing agent into the mixed solution, stir at 3500rpm and 25°C (room temperature) for 15min to obtain a graphene oxide / polyaniline composite modified water-based epoxy resin anti-corrosion coating, recorded as 0.3% WEP / (GO:PANI=9:1), 0.3% is the ratio of graphene oxide / polyaniline composite hybrid to the total solid content of epoxy emulsion and graphene oxide / polyaniline composite hybrid.
[0151] Example 4
[0152] The mass of the graphene oxide / polyaniline composite hybrid solution in S2 of Example 3 was adjusted to 6.28, 8.81, and 12.63 g, and the others were consistent with Example 3 to obtain a graphene oxide / polyaniline composite modified water-based epoxy resin anti-corrosion coating, recorded as 0.5% WEP / (GO:PANI=9:1), 0.7% WEP / (GO:PANI=9:1), and 1.0% WEP / (GO:PANI=9:1).
[0153] Example 5
[0154] The mass of the graphene oxide / polyaniline composite hybrid solution in S2 of Example 3 is adjusted to 6.28 g, and the graphene oxide / polyaniline composite hybrid used is the one in Example 2, and the rest is consistent with Example 4 to obtain a graphene oxide / polyaniline composite modified water-based epoxy resin anti-corrosion coating; recorded as 0.5% WEP / (GO:PANI=7:3), 0.5% WEP / (GO:PANI=1:1), 0.5% WEP / (GO:PANI=3:7), 0.5% WEP / (GO:PANI=1:9).
[0155] Comparative Example 5
[0156] A method for preparing a waterborne epoxy resin anticorrosive coating comprises the following steps:
[0157] Take 20g of epoxy emulsion and add it into a 100mL three-necked flask, stir at 3500rpm and 25℃ (room temperature) for 10min; then add 3.82g of waterborne epoxy curing agent, stir at 3500rpm and 25℃ (room temperature) for 15min to obtain a waterborne epoxy resin anti-corrosion coating, recorded as WEP.
[0158] Comparative Example 6
[0159] A method for preparing a water-based graphene oxide anti-corrosion coating comprises the following steps:
[0160] The graphene oxide with a pH of 5 obtained by centrifugation in step (2) of Example 1 was added into water to obtain a graphene oxide aqueous dispersion with a concentration of 8 mg / mL;
[0161] Take 20g of epoxy emulsion and add it to a 100mL three-necked flask, stir at 3500rpm and 25°C (room temperature); take 6.28g of graphene oxide aqueous dispersion and add it drop by drop (dropping speed is 1mL / min) into the epoxy emulsion, stir at 3500rpm and 25°C (room temperature) for 3h, then add 3.82g of water-based epoxy curing agent, stir at 3500rpm and 25°C (room temperature) for 15min, and obtain a water-based graphene oxide anti-corrosion coating, recorded as 0.5% WEP / GO.
[0162] Comparative Example 7
[0163] A method for preparing a water-based graphene oxide anti-corrosion coating comprises the following steps:
[0164] The graphene oxide with a pH of 5 obtained by centrifugation in step (2) of Example 1 was added into water to obtain a graphene oxide aqueous dispersion with a concentration of 8 mg / mL;
[0165] 0.5 g of polyaniline powder was added to 100 g of a mixed solvent of m-cresol and 1,4-dioxane (mass ratio was 4:1), and ultrasonically dispersed for 15 min at 20 W and 25° C. (normal temperature) using an ultrasonic cleaning machine to obtain a polyaniline dispersion;
[0166] Take 20g of epoxy emulsion and add it to a 100mL three-necked flask, stir at 3500rpm and 25℃ (room temperature); take 0.9g of graphene oxide aqueous dispersion (5mg / mL) and 1g of polyaniline solution and add them drop by drop (dropping speed is 1mL / min) into the epoxy emulsion, stir at 3500rpm and 25℃ (room temperature) for 3h, then add 3.82g of water-based epoxy curing agent, stir at 3500rpm and 25℃ (room temperature) for 15min, and obtain a water-based graphene oxide anti-corrosion coating, recorded as 0.5% WEP / GO@PANI.
[0167] The obtained anti-corrosion coating was subjected to an anti-corrosion performance test, and the test results are as follows:
[0168] Table 3
[0169] example Salt spray resistance time Example 3 (0.3% WEP / (GO:PANI=9:1)) More than 960 hours Example 4 (0.5% WEP / (GO:PANI=9:1)) More than 960 hours Example 4 (0.7% WEP / (GO:PANI=9:1)) More than 960 hours Example 4 (1% WEP / (GO:PANI=9:1)) More than 960 hours Example 5 (0.5% WEP / (GO:PANI=7:3)) More than 960 hours Example 5 (0.5% WEP / (GO:PANI=1:1)) More than 960 hours Example 5 (0.5% WEP / (GO:PANI=3:7)) More than 960 hours Example 5 (0.5% WEP / (GO:PANI=1:9)) More than 960 hours Comparative Example 5 Less than 240 hours Comparative Example 6 Less than 480 hours Comparative Example 7 Less than 480 hours
[0170] Fig. 9 The test results of the anti-corrosion performance of the anti-corrosion coatings prepared in Examples 3, 4 and Comparative Example 5 at 0, 10, 20, 30 and 40 days are as follows: Fig. 9 It can be seen that the anti-corrosion coatings of Examples 3 and 4 slightly turned white and gray during the salt spray test, and no obvious corrosion occurred even after 960 hours, indicating that the coatings have excellent corrosion resistance.
[0171] Fig.10 The test results of the anti-corrosion performance of the anti-corrosion coatings prepared in Examples 4 and 5 and Comparative Examples 5 and 6 at 0, 10, 20, 30 and 40 days are as follows: Fig.10 It can be seen that the anti-corrosion coatings of Examples 4 and 5 turned slightly white to gray during the salt spray test, and no obvious corrosion occurred even after 960 hours, indicating that the coatings had excellent corrosion resistance; the coatings of Comparative Examples 5 and 6 turned slightly white to gray during the salt spray test, and no obvious corrosion occurred even after 960 hours, indicating that the coatings had excellent corrosion resistance.
[0172] Example 6
[0173] A method for preparing a supercapacitor comprises the following steps:
[0174] The aqueous graphene oxide / polyaniline composite hybrid prepared in Example 1 was dissolved in water to obtain a solution with a concentration of 10 mg / mL; vacuum filtration was performed to form a film, and drying was performed at 60° C. to obtain a flexible electrode film with a thickness of 20 μm;
[0175] The flexible electrode film was loaded on the supercapacitor as the working electrode, the carbon black film was loaded on the counter electrode, Ag / AgCL was used as the reference electrode, and the electrolyte solution was 1 mol / L sulfuric acid solution at 20 mV·S -1 Cyclic voltammetry was performed at a scan rate of ; impedance testing was performed at a voltage of 10 mV and a frequency of 0.1-50000 Hz.
[0176] Test results such as Fig.11 ,from Fig.11 It can be seen that the prepared supercapacitor exhibits low charge transfer resistance and ideal capacitive behavior.
[0177] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing an aqueous graphene oxide / polyaniline composite hybrid, characterized in that: The steps include: (1) Oil phase: Ultrasonic dispersion of polyaniline powder in a solvent to obtain a polyaniline solution; wherein the solvent is a single phenol solvent or a mixed solvent of a phenol solvent and a low dielectric constant solvent as an oil phase; the low dielectric constant solvent is one or more of n-hexane, 1,4-dioxane, toluene, anisole, and chloroform; (2) Aqueous dispersed phase: dispersing graphene oxide in water to obtain a graphene oxide aqueous dispersion as an aqueous dispersed phase; (3) Preparation of hybrids: The polyaniline solution is added dropwise to the graphene oxide aqueous dispersion, stirred and ultrasonicated to obtain an oil-in-water emulsion; the oil-in-water emulsion is then subjected to solvent evaporation or centrifugal washing to obtain an aqueous graphene oxide / polyaniline composite hybrid; wherein the dropping speed is 0.8-1.2 mL / min.
2. The method according to claim 1, characterized in that In step (1), the phenol solvent is any one or more of m-cresol, o-cresol, p-cresol and resorcinol; and the mass ratio of the phenol solvent to the low dielectric constant solvent in the mixed solvent of the phenol solvent and the low dielectric constant solvent is 3-5:
1.
3. The method according to claim 1, characterized in that The preparation method of the graphene oxide aqueous dispersion in step (2) is as follows: adding the graphene oxide filter cake to water at a concentration of 5-10 mg / mL, ultrasonically treating at 15-25W and 20-30°C for 15-20 min, washing and centrifuging at 10000rpm-11000rpm for 10-20 min to obtain graphene oxide with a pH of 4-9, dispersing the graphene oxide in water to obtain a graphene oxide aqueous dispersion with a concentration of 0.1-1 mg / mL.
4. Aqueous graphene oxide / polyaniline composite hybrid prepared by the method according to any one of claims 1 to 3.
5. A method for preparing a graphene oxide / polyaniline composite modified waterborne epoxy resin anticorrosive coating, characterized in that: The following steps are involved: S1: dispersing the aqueous graphene oxide / polyaniline composite hybrid according to claim 4 into water to obtain a graphene oxide / polyaniline composite hybrid solution; S2: Add the graphene oxide / polyaniline composite hybrid solution dropwise into the epoxy emulsion and mix evenly; then add the water-based epoxy curing agent solution and stir evenly to obtain a graphene oxide / polyaniline composite modified water-based epoxy resin anti-corrosion coating.
6. The graphene oxide / polyaniline composite modified water-based epoxy resin anti-corrosion coating prepared by the method according to claim 5.
7. Application of the graphene oxide / polyaniline composite modified water-based epoxy resin anti-corrosion coating according to claim 6 in the field of metal corrosion protection.
8. A supercapacitor, characterized in that: The aqueous graphene oxide / polyaniline composite hybrid described in claim 4 is used.
9. A method for improving the dispersibility of polyaniline in graphite oxide dispersion, characterized in that: The steps include: (1) Oil phase: Ultrasonic dispersion of polyaniline powder in a solvent to obtain a polyaniline solution; wherein the solvent is a single phenol solvent or a mixed solvent of a phenol solvent and a low dielectric constant solvent as an oil phase; the low dielectric constant solvent is one or more of n-hexane, 1,4-dioxane, toluene, anisole, and chloroform; (2) Aqueous dispersed phase: dispersing graphene oxide in water to obtain a graphene oxide aqueous dispersion as an aqueous dispersed phase; (3) Preparation of hybrids: The polyaniline solution is added dropwise to the graphene oxide aqueous dispersion, stirred and ultrasonicated to obtain an oil-in-water emulsion; the oil-in-water emulsion is then subjected to solvent evaporation or centrifugal washing to obtain an aqueous graphene oxide / polyaniline composite hybrid; wherein the dropping speed is 0.8-1.2 mL / min.
Citation Information
Patent Citations
Preparation method of graphene oxide / polyaniline composite material and graphene oxide / polyaniline-epoxy resin composite coating
CN116948518A
Interface regulation-based composite anticorrosive coating, and preparation method and application thereof
CN111548704A
Gr / PANI@ EPOSS hybrid material, preparation method thereof, self-repairing hydrophobic composite coating and use method thereof
CN112552734A